Choosing sides: unusual ultrafast charge transfer pathways in an asymmetric electron-accepting cyclophane that binds an electron donor. Issue 15 (15th March 2019) - Zhou, Jiawang; Wu, Yilei; Roy, Indranil; Samanta, Avik; Stoddart, J. Fraser; Young, Ryan M.; Wasielewski, Michael R.
Abstract : Photo-driven electron transfer is faster from an electron donor guest to the harder to reduce acceptor in an asymmetric cyclophane host. Abstract : Constructing functional molecular systems for solar energy conversion and quantum information science requires a fundamental understanding of electron transfer in donor–bridge–acceptor (D–B–A) systems as well as competitive reaction pathways in acceptor–donor–acceptor (A–D–A) and acceptor–donor–acceptor′ (A–D–A′) systems. Herein we present a supramolecular complex comprising a tetracationic cyclophane having both phenyl-extended viologen (ExV 2+ ) and dipyridylthiazolothiazole (TTz 2+ ) electron acceptors doubly-linked by means of two p -xylylene linkers (TTzExVBox 4+ ), which readily incorporates a perylene (Per) guest in its cavity (Per ⊂ TTzExVBox 4+ ) to establish an A–D–A′ system, in which the ExV 2+ and TTz 2+ units serve as competing electron acceptors with different reduction potentials. Photoexcitation of the Per guest yields both TTz + ˙–Per + ˙–ExV 2+ and TTz 2+ –Per + ˙–ExV + ˙ in <1 ps, while back electron transfer in TTz 2+ –Per + ˙–ExV + ˙ proceeds via the unusual sequence TTz 2+ –Per + ˙–ExV + ˙ → TTz + ˙–Per + ˙–ExV 2+ → TTz 2+ –Per–ExV 2+ . In addition, selective chemical reduction of TTz 2+ gives Per ⊂ TTzExVBox 3+ ˙, turning the complex into a D–B–A system in which photoexcitation of TTz + ˙ results in the reaction sequence 2 *TTz + ˙–Per–ExV 2+ → TTz 2+ –Per–ExV + ˙ → TTz + ˙–Per–ExV 2+ . Both reactions TTz 2+ –Per + ˙–ExV + ˙ → TTz + ˙–Per + ˙–ExV 2+ and TTz 2+ –Per–ExV + ˙ → TTz + ˙–Per–ExV 2+ occur with a (16 ± 1 ps) −1 rate constant irrespective of whether the bridge molecule is Per + ˙ or Per. These results are explained using the superexchange mechanism in which the ionic states of the perylene guest serve as virtual states in each case and demonstrate a novel supramolecular platform for studying the effects of bridge energetics within D–B–A systems.